Association between high-density-lipoprotein cholesterol and postoperative recovery from lumbar disc herniation - Nuoman Han; Wei Chen; Shuai Zhou; Rui Chen; Guangzhao Hou; Qian Xiao; Zhenbang Yang; Shihang Liu; Yingze Zhang; Hongzhi Lv (PLoS ONE, 2026)
Objective The levels of high density lipoprotein cholesterol (HDL-C) correlate with lumbar spine degeneration, but their value for predicting the prognosis of the lumbar spine is unclear. This study was implemented to explore whether HDL-C levels were associated with postoperative recovery from lumbar disc herniation (LDH). Methods Patients with LDH who underwent posterior lumbar interbody fusion (PLIF) admitted between January 1 st , 2018, and December 31 st , 2022, were included in this study. The outcome was postoperative recovery as assessed by the economic-functional score. The primary exposure variable was the postoperative plasma HDL-C level. LASSO regression was used to screen for variables associated with outcome, and GAM modeling was used to determine cutoff values for HDL-C levels, with the adjusted model used to estimate the relative contribution of each variable. HDL-C levels were transformed into a dichotomous variable based on the cutoff values, and multifactorial logistic regression was used to assess OR. Results A total of 967 patients with LDH were included 529 males (54.7%), 438 females (45.3%), mean age 49.63 ± 12.51 years, mean HDL-C level 1.14 ± 0.25 mmol/L. LASSO regression showed that HDL-C was associated with outcome, there was a risk-protecting effect in the GAM with a cutoff value of 1.15 mmol/L. According to the commonly used clinical classification method, logistic regression showed that normal levels of HDL-C were protective compared with abnormal levels (OR=1.553, 95% CI,1.017–2.372, P = 0.042). HDL-C had a U-shaped effect in patients without cerebral disease, with a range of 1.1–1.8 mmol/L promoting recovery,and in the subgroup without cerebral disease, HDL-C level ranked 6 out of 20 variables, whereas in the overall cohort it ranked 14th and showed no significant effect. Logistic regression showed a protective effect of normal levels of HDL-C over abnormal levels (OR=1.900, 95% CI,1.206–2.992, P = 0.006). Conclusion Postoperative HDL-C levels were not significantly associated with 1-year postoperative functional recovery in the overall cohort of patients undergoing PLIF for LDH. In a pre-specified subgroup of patients without cerebral disease, postoperative HDL-C levels exhibited a significant U-shaped association with recovery (optimal range 1.1–1.8 mmol/L). These findings are hypothesis-generating and require validation in future studies.